Role and mechanism of gut microbiota in regulating interferon-mediated programmed cell death in colorectal cancer - Yao, Qipeng; Chen, Shiyin; Qian, Weiwei; Yang, Chao; Li, Junxian (Frontiers in Immunology, 2026)
Colorectal cancer (CRC) is a highly prevalent and lethal malignancy worldwide, whose development is closely associated with gut microbiota dysbiosis and immune microenvironment imbalance. Interferons (IFNs) serve not only as pivotal cytokines bridging innate and adaptive immunity but also induce multiple forms of programmed cell death (PCD), playing a crucial role in antitumor immunity. This narrative review examines the core mechanisms of the gut microbiota-IFNs-programmed cell death axis within the CRC immune microenvironment. As upstream regulators, gut microbiota profoundly influence the production and function of type I, II, and III interferons through metabolic products and microbial-associated molecular patterns (MAMPs). Conversely, IFNs, serving as the pivotal link between innate and adaptive immunity, directly participate in tumor immune surveillance while also determining tumor cell fate by finely regulating PCD pathways such as apoptosis, autophagy, pyroptosis, and ferroptosis. In the CRC context, protective microbiota enhances IFN signaling and promote immunogenic PCD, activating effective antitumor immunity. Conversely, carcinogenic microbiota suppresses IFN responses, disrupt immune surveillance, and drive immune evasion and drug resistance. In-depth investigation of the mechanisms by which gut microbiota modulate interferon-mediated programmed cell death in CRC not only offers new insights into CRC immune evasion but also provides a theoretical foundation for developing combined immunotherapy strategies based on microbiota intervention, targeting IFN pathways, or regulating PCD patterns.